Analytical solutions in the two-cavity coupling problem - Ayzatsky, N.I. (Вопросы атомной науки и техники, 2000)
Analytical solutions of precise equations that describe the rf-coupling of two cavities through a coaxial cylindrical hole are given for various limited cases. For their derivation we have used the method of solution of an infinite set of linear algebraic equations, based on its transformation into dual integral equations.